Pertanggungjawaban Pidana Korporasi di Kota Kupang dalam Mendukung Implementasi UU No 27 Tahun 2007 tentang Pengelolaan Pesisir dan Pulau-Pulau Kecil - Gabriela Patricilla Mali; Jimmy Pello; Bhisa V. Wilhelmus (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This study aims to find out and analyze the criminal liability of corporations in Kupang City in supporting the implementation of Law No. 27 of 2007 concerning the Management of Coasts and Small Islands. This research is an empirical judicial research supported by an empirical and normative approach that uses primary data and secondary data collected using interview techniques and literature studies and then processed using editing and coding techniques and analyzed in a qualitative descriptive manner. The results of this study show that (1) Law Number 27 of 2007 concerning the Management of Coastal Areas and Small Islands has an important role in regulating the protection and utilization of coastal areas. However, the application of this law in criminal enforcement against the perpetrators of coastal ecosystem destruction still faces various obstacles (2) The legal arrangements in this Law aim to protect, manage, and utilize coastal areas in a sustainable manner. Law Number 27 of 2007 provides a legal basis for the planning, protection, and utilization of coastal ecosystems and involves community participation in the management of natural resources.